(untitled) (Global Journal of Management and Business Research, 2021)
The paper investigated the perception of women toward the commercialisation of the NICANVEG indigenous vegetables project. A survey research design was used for the study. Samples of 390 women (300 for quantitative and 90 for qualitative) were used for the study. The samples were selected from three out of the four states in Southwestern Nigeria where the project took place between 2011 and 2014. Two adapted instruments titled "Questionnaire on NICANVEG Project and Commercialisation (QNPC)" and "Interview on NICANVEG Project and Commercialisation" (INPC) were used to collect data. Data collected were analysed using percentages, relative significant index, chi-square and software package (Atlas ti) statistical analyses. The results showed that 182 (60.7%) of the women expressed a positive perception towards the commercialisation of the product.